The Effectiveness of Picture Series in Teaching Speaking - Sari, Komang Bela Pradnya; Dewi, Ni Luh Putu Eka Sulistia; Marsakawati, Ni Putu Era (STKIP AGAMA HINDU SINGARAJA, 2023)
Speaking is one of the activities of conveying ideas into a few words that are spoken. Many students get bored easily in dealing with English, especially in speaking. Picture series are expected to help students in speaking. The research design was quantitative experimental. This study used class tenth students at SMK TI Bali Global as the population. The researcher used two classes as samples, namely X Akuntansi and X Multimedia, each class consisting of 14 students. There were four meetings for the control class and the experimental class. This study analyzed data with SPSS. In the paired sample t-test was 0.000 with a significance of 0.05 must be less than 0.05. In the words, there was a significant difference in speaking skills between students who are taught before treatment and after treatment. This means that “Ho” was rejected and “Ha” was accepted. The answer to the research problem was picture series is effective in teaching speaking for the tenth grade of SMK TI Bali Global. This study encourages teachers to apply effective strategy such as using picture series in teaching speaking.